STRATEGI BERJARINGAN RADIO KOMUNITAS ISLAM MADU FM TULUNGAGUNG - Redi Panuju (Jurnal Sosiologi Reflektif, 2018)
The purpose of this study to determine the strategy of community radio broadcasting in particular contestation Madu FM community radio in Tulungagung in East Java Indonesia. Madu FM community radio phenomenon is interesting to study because it is a community radio station that managed to grow in the midst contestation broadcasting. Community radio gets limitation restriction (restriction) of the state through the Broadcasting Act (Act No. 32 of 2002 on Broadcasting). Besides, the community radio still has to compete with the private radio and private television. Madu FM is able to adapt to circumstances without violating the rules. The result is a strategy of community radio broadcasting successfully innovate innovation so that it becomes exist. This research approach is qualitative approach with the method of observation and in-depth interviews. The study was conducted during the period from March to August, 2016.Tujuan penelitian ini untuk mengetahui strategi penyiaran radio komunitas khususnya dalam kontes radio komunitas Madu FM di Tulungagung di Jawa Timur Indonesia. Fenomena radio komunitas Madu FM sangat menarik untuk diteliti karena merupakan stasiun radio komunitas yang berhasil tumbuh di tengah penyiaran kontestasi. Radio komunitas mendapat pembatasan pembatasan (pembatasan) negara melalui Undang-Undang Penyiaran (UU No. 32 Tahun 2002 tentang Penyiaran). Selain itu, radio komunitas masih harus bersaing dengan radio swasta dan televisi swasta. Madu FM mampu beradaptasi dengan keadaan tanpa melanggar peraturan. Hasilnya adalah strategi penyiaran radio komunitas berhasil berinovasi inovasi sehingga menjadi ada. Pendekatan penelitian ini adalah pendekatan kualitatif dengan metode observasi dan wawancara mendalam. Penelitian dilakukan selama periode dari bulan Maret sampai Agustus 2016.Keywords: Community Radio, contestation, strategies, adaptation and rational choice.